Organizational Prevention and Management Strategies for Workplace Aggression Among Child Protection Workers: A Project Protocol for the Oslo Workplace Aggression Survey (OWAS) - Nielsen, Morten Birkeland; Christensen, Jan Olav; Hetland, Jørn; Finne, Live Bakke (Frontiers in Psychology, 2020)
Background: Previous research has established exposure to workplace aggression as a significant risk factor for employee functioning, well-being, and health. However, less is known about effective prevention- and management strategies. The main objectives of the current project are to determine the impact of physical and psychological aggression on the well-being, health and work ability of employees in the child welfare service and to establish whether a strong psychosocial safety climate and ethical infrastructure are effective with regard to protecting employees against aggression. This project may help identify the specific risks child welfare workers are exposed to, the impact of workplace aggression on their health and well-being, and the most effective strategies to manage the problem. Furthermore, the findings should be central for developing laws and regulations and to any political decision on measures to tackle aggression in the workplace. Methods: The study will employ two prospective data collections. First, a three-wave longitudinal survey with a six month time-lag between measurement points will be conducted among all 1500 employees in the child welfare services in Oslo Municipality, Norway. Data will have a multilevel structure and will be linked to registry data on sickness absence. Second, a quantitative daily diary study over a 14-day period will include 150 of the respondents from the main survey study. The survey questionnaires will mainly comprise well-established and psychometrically validated indicators of workplace aggression, health and well- being, psychosocial safety climate, ethical infrastructure and other relevant factors. The Regional Committees for Medical and Health Research Ethics (REC) in Norway (REC South East) have approved this project (project number 28496). Discussion: This project will identify the impact of workplace aggression on child protection workers, as well as provide information on how organizations can actively manage exposure to workplace aggression. The findings may serve as a starting point for intervention studies as well as for the development of policies and guidelines for how to handle workplace aggression.